Fruits and vegetable consumption, and its association with hypertension among women in Ghana: a cross-sectional study - Joshua Okyere; Castro Ayebeng; Bernard Afriyie Owusu; Kwamena Sekyi Dickson (Cambridge University Press, 2024)
Abstract Objective: This study aimed to examine the association between fruit and vegetable consumption (FVC) and the risk of hypertension among women in Ghana. Design: Data from the 2014 Ghana Demographic and Health Survey were used. Bivariate and multivariate logistic regression analyses were performed using Stata version 14. The study reports the adjusted OR (AOR) and CI. Setting: Ghana Participants: A total sample of 4168 women was used in the analysis. Results: Among women who met the WHO's recommended intake of FVC, 13·1 % had hypertension. The intake of the recommended servings of fruit and vegetables was not significantly associated with hypertension. However, the likelihood of being hypertensive was significantly associated with increasing age (AOR = 6·1; 95 % CI = 4·29, 8·73), being married (AOR = 1·7; 95 % CI = 1·14, 2·57) or formerly married (AOR = 2·3; 95 % CI = 1·44, 3·70), and being overweight (AOR = 1·6; 95 % CI = 1·24, 2·07) or obese (AOR = 2·4; 95 % CI = 1·82, 3·20). Conclusion: The study concludes that there is no significant association between FVC and hypertension risk among women in Ghana. While this study did not find a significant association between FVC and hypertension risk among women in Ghana, it underscores the point that other multifaceted factors influence hypertension risk. As such, public health campaigns should emphasise a balanced and holistic approach to promoting cardiovascular health, including factors beyond FVC. The findings also highlight the need to target high-risk populations (i.e. older women, married and formerly married women, and overweight or obese women) with hypertension prevention education and related interventions.